El problema del cambio climático y los derechos humanos, una difícil conexión - Acevedo Albornoz , Irene; Riquelme Rivera, Jorge (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This research concerns the problem of climate change and human rights, in particular the emerging human rights, a concept that is still being discussed in the international UN system. Although there is already some plausible reference for International Environmental Law under the premise that human rights are interdependent, there is still a long way to go in the fight to install, in the international community, the idea that climate change is not just an economic and social problem, but is a question that violates one of the basic foundations of the state which is to protect and promote a clean environment for its citizens.